Impact of skeletal muscle volume on patients with BCLC stage‐B hepatocellular carcinoma undergoing sorafenib therapy - Issei Saeki; Takahiro Yamasaki; Yurika Yamauchi; Tomokazu Kawaoka; Shinsuke Uchikawa; Akira Hiramatsu; Hiroshi Aikata; Kazufumi Kobayashi; Takayuki Kondo; Sadahisa Ogasawara; Tetsuhiro Chiba; Reo Kawano; et al. (Cancer Medicine, 2023)
Abstract Aim Skeletal muscle volume has been reported to be an important factor that determines overall survival (OS) and post‐progression survival (PPS) in patients with hepatocellular carcinoma (HCC). However, the impact of skeletal muscle volume on HCC with Barcelona Clinic Liver Cancer (BCLC) stage B (BCLC‐B) remains unclear. We conducted sub‐analyses of a previous study on BCLC‐B and compared our findings with data on HCC with BCLC stage C (BCLC‐C). Methods We retrospectively enrolled 356 patients with HCC (BCLC‐B, n = 78; and BCLC‐C, n = 278) undergoing sorafenib therapy. Prognostic factors were analyzed using various parameters, including skeletal muscle volume. Muscle volume (MV) depletion was designated as less than the median value of the skeletal muscle index for each gender (cutoff value: 45.0 cm2/m2 for male and 38.0 cm2/m2 for female participants). Results Both OS and PPS showed no significant differences in patients with non‐MV depletion and those with MV depletion in the BCLC‐B group (Median OS [MST] 19.3 vs. 13.5 months [p = 0.348]; median PPS 9.7 vs. 10.8 months [p = 0.578]). In the BCLC‐C group, patients with non‐MV depletion had a significantly longer OS and PPS compared to patients with MV depletion (MST 12.4 vs. 9.0 months [p = 0.001] and median PPS 7.9 vs. 5.4 months [p = 0.002]). Multivariate analysis revealed that MV depletion was an independent prognostic factor of OS and PPS in the BCLC‐C group but not in the BCLC‐B group. Conclusions Skeletal muscle volume showed little impact on the clinical outcomes of patients with BCLC‐B undergoing sorafenib therapy.